Comparison of sedative effects of oral midazolam/chloral hydrate and midazolam/promethazine in pediatric dentistry - Mehran, Majid (J Dent Res Dent Clin Dent Prospects, 2018)
Background. The aim of this investigation was to compare the sedative effects of oral midazolam/chloral hydrate and midazolam/promethazine combinations on fearful children needing dental treatment. Methods. This crossover double-blind clinical trial was conducted on 30 children aged 2‒6 years, who had at least two similar teeth needing pulp treatment. Standard vital signs were recorded before and after premedication. Wilson sedation scale was used to judge the level of sedation. Cases were divided into two groups based on the sequence of medication received. This was to overcome the sequence effect. Group I received oral midazolam (0.4 mg/kg/chloral hydrate (50 mg/kg) at the first visit while they received midazolam (0.4 mg/kg)/promethazine (5 mg/kg) in their second visit. Group II received the premedication in the opposite sequence. The operator and child were blinded to the medication administered. Sedative efficacy of the two combinations were assessed and judged by two independent pediatric dentists based on the Wilson scale. Data were analyzed with ANOVA and paired t-test. Results. Only 10% of children who received chloral hydrate with midazolam exhibited high improvement in their behavior while 53% showed reasonable positive changes and 12% had no change or even deterioration of behavior. The difference between the effect of the two combination drugs was statistically significant (P<0.05) in favor of the chloral hydrate group. Conclusion. The results showed a significant difference in the sedation level induced between the two groups. Midazolam/chloral hydrate combination more effectively improved the co-operation for dental treatment.